Biological insights into the piericidin family of microbial metabolites - Sepideh. M. Azad; Yu Jin; Hooi_Leng Ser; Bey_Hing Goh; Learn_Han Lee; Chitti Thawai; Ya_Wen He (My University, 2021)
Extensively produced by members of the genus Streptomyces, piericidins are a large family of microbial metabolites, which consist of main skeleton of 4‐pyridinol with methylated polyketide side chain. Nonetheless, these metabolites show differences in their bioactive potentials against micro‐organisms, insects and tumour cells. Due to its close structural similarity with coenzyme Q, piericidins also possess an inhibitory activity against NADH dehydrogenase as well as Photosystem II. This review studied the latest research progress of piericidins, covering the chemical structure and physical properties of newly identified members, bioactivities, biosynthetic pathway with gene clusters and future prospect. With the increasing incidence of drug‐resistant human pathogen strains and cancers, this review aimed to provide clues for the development of either new potential antibiotics or anti‐tumour agents.
Keywords: Polyketide synthase; Human pathogen; Microbial Natural Products and Biosynthesis